T‐cells infiltration mediates the association between neutrophil/lymphocyte ratio and survival in gastric cancer - Qifei He; Longtao Huangfu; Biao Fan; Qianzheng Zhuang; Liu He; Lin Li; Wei You; Xiaofang Xing (Cancer Medicine, 2023)
Abstract Background Neutrophil/lymphocyte ratio (NLR) is a vital index for systemic inflammation and a prognostic indicator for gastric cancer (GC). Despite the abundant literature on NLR's prognostic value for GC, the underlying factors mediating its impact on survival remain unclear. The objective of this study was to analyze the role of NLR in different prognostic models and subgroups, and investigate the mediating effects of immune infiltrates between NLR and survival. Methods A total of 924 patients who underwent D2 lymph node resection were enrolled in this study. According to the level of NLR, patients were divided into two groups, the high and low NLR groups. Clinical parameters, indexes related to immune infiltrates, and survival were compared between the two groups. Prognostic models, interaction analysis, and mediating effects analysis were performed to investigate the clinical association of NLR, immune infiltrates, and survival. Results The infiltration of CD3+ and CD8+ T cells was significantly different in the two NLR groups. The level of NLR was an independent prognostic predictor of GC. In addition, an interaction effect exists between NLR and MMR status on the prognosis of GC (p‐interaction <0.01). Lastly, the mediating effect analysis revealed that the infiltration level of CD3+ T cells was the mediating factor between NLR and survival (p < 0.001). Conclusions The level of NLR is an independent prognostic predictor of GC. The effect of NLR on prognosis is partly mediated by CD3+ T‐cell infiltration.